PVA/WHEY PROTEIN NANOFIBER-COATED PP MELT BLOWN INTEGRATED WITH PICKERING EMULSION OF CITRAL STABILIZED FOR POTENTIAL MEDICAL APPLICATIONS - Parın, Fatma Nur; Yesilyurt, Aysenur; Parın, Uğur (My University, 2024)
As an antibacterial agent with pleasant fragrance, citral (CIT) indicates hydrophobic character, and therefore has low water solubility. In this study, Pickering emulsions were formed and polyvinyl alcohol (PVA)/whey protein hydrophilic nanofibers were coated on PP melt blown non-woven surfaces by electrospinning method. In this context, hydrophobic citral essential oil is stabilized with ?-cyclodextrin (?-CD) in the electrospinning process. PVA and whey protein polymer blend were used as nanofiber matrices. The morphological, physical, and thermal properties of the ?-CD/citral complexes were investigated in PVA/whey protein nanofiber-coated PP non-wovens at various ?-CD levels (1:2, 1:4 and 1:6). Furthermore, zone inhibition procedure was performed to evaluate antibacterial activity of the samples against Gram (+) (Staphylococcus aureus ATCC® 25923) and Gram (-) (Escherichia coli ATCC® 25922, and Pseudomonas aeruginosa ATCC® 27853) bacteria. The morphology of fibers showed that all obtained nanofiber-coated PP surfaces were in the range with 216 - 330 nm average fiber diameter. Fourier Transform Infrared (FT-IR) and thermal gravimetric analysis (TGA) thermograms revealed that citrals were successfully integrated into the bio-based nanofibers. As the amount of citral increased (i.e., the ?-CD/citral increased), the thermal resistance of bio-based nanofiber coated PP surfaces increased. Antibacterial activity indicated the citral-loaded nanofiber-coated PP surfaces were most effective against Escherichia coli, while none of the samples have antibacterial activity against Pseudomonas aeruginosa. Overall, the results displayed that the fabricated PVA/whey protein nanofiber-coated PP samples integrated with Pickering emulsion of citral stabilized have promising wound dressing applications.
Keywords: Antibacterial property; Pickering emulsion; PP melt blown; PVA/whey protein nanofiber; ?-CD/citral complex